Water droplets in oil at the inlet of an EHD contact: A dual experimental and numerical investigation. (January 2023) - Zhang, F.; Fillot, N.; Bouscharain, N.; Devaux, N.; Philippon, D.; Matta, C.; Morales-Espejel, G.E.
Abstract: The current study employs both experimental and numerical approaches to investigate water-in-oil flow at the entrance of EHD contacts. In this work, for the first time, a micro-sized water-in-oil emulsion flow was directly observed at the entrance of an EHL point contact using a high-speed camera. To represent the severity of the water-in-oil emulsion, the abscissa of the closest droplets to the contact area is compared to the critical meniscus position of starvation calculated for pure oil EHL condition. A numerical approach was developed based on the experimental observation. The impacts of various operating parameters such as rolling velocity, water droplet size, applied load, and lubricant viscosity on the flow of water-in-oil emulsion have been further investigated. The results of this work give a possible explanation for the contradictory findings in the literature and reveal the critical conditions under which water-in-oil emulsion would influence the EHL contacts.